COMPARISON OF NATIONAL LAWS IN INDONESIA AND THAILAND REGARDING AIRLINE LIABILITY FOR FLIGHT DELAYS - Sulastri; Riza, Faisal (International Journal of Cultural and Social Science, 2026)
The aviation industry is one of the most important sectors to support mobility and increase economic growth, the tight flight schedule causes the emergence of several new problems, one of which is flight delay. For this reason, further research is needed regarding the airline's responsibility to passengers if a flight schedule delay occurs, in this case the researcher focuses on the regulations in force in Indonesia and Thailand. The purpose of this study is to determine the regulations in force in Indonesia and Thailand, and to find similarities and differences between the two regulations. This study uses a normative juridical research type with a Statute Approach, and a comparative approach (Comparative Approach). Data sources include revelation data (QS. Al-Mudassir: 38) and secondary data covering the schedule of flight accuracy and delays that occur in Indonesia and Thailand. The results of this study indicate that the regulations in force in Indonesia are regulated in Law Number 1 of 2009 and Regulation of the Minister of Transportation Number 89 of 2015 and Law Number 8 of 1999 while in Thailand it is regulated in the Civil Aviation Council Regulation No. 101 and the Consumer Protection Act (B.E. 2522 (1979)). Of the several similarities, the most important is that delays of more than 2 hours in Indonesia and Thailand both provide compensation in the form of free food and drinks for passengers, and the most important difference is that in Thailand for delays of more than 2 hours the airline is required to provide equipment for communication, while in Indonesia it is not required to provide communication equipment such as telephone or email.